The garden of knowledge and virtue: a tale of necessity and duty - Eid, Iyad Muhammad; Rokis, Rohaiza (IIUM Press, 2020)
This paper addresses the perceptions and practices of doctorate candidates at the International Islamic University Malaysia (IIUM) toward its vision of devoting educational efforts for restoring the dynamic role of the Muslim Ummah in all fields of knowledge and intellectual discourse. It investigates to what extent they possess competent research skills and foster core values such as cooperation and trust. It utilizes the qualitative research approach, using thematic analysis of data collected by semi-structured interviews. The sample is composed of ten Ph.D candidates, coming from the Middle East and Asian countries who currently study at IIUM. They are all Muslims; four females and six males. Eight candidates are the international students and two are Malaysians. Purposive sampling was implemented to select the candidates who were still pursuing their Ph.D degree at the time of conducting the study. They all came from five different kulliyyah (faculties), with two from each kulliyyah. The study showed that the Ph.D candidates’ practices did not reflect the vision of IIUM. They lacked of competent research knowledge and skills as well as the core values represented by cooperation and mutual trust, which were clearly manifested in the IIUM’s vision. The implication of this current qualitative study may bring into the realization of the existing critical situation of the Muslim Ummah. The Maqasid al- Shariah may be seen as the practical formula for IIUM to restore the core educational system for Islamic revivalism and glory.